Isolation, characterizations, and antimicrobial activities of a phytosterol Dendrosterone isolated from plant Dendrobium ochreatum - Janmajoy Banerjee; Dipanjan Karati (Elsevier, 2022)
Background: - The present work aimed to isolate one steroidal molecule from Dendrobium ochreatum. From phytochemical analysis, the presence of steroids was observed only in chloroform extracts of the stem, and the antimicrobial activities supported the extracts to be the most significant one, so work was aimed at isolating the chloroform extracts of the stem. Method: About 250 gm of each leaf stem and root powder was filled in the thimble and extracted with hexane, chloroform, and ethanol using a Soxhlet extractor for 72 hrs. The extract solution was filtered through Whatman filter paper no.1, then concentrated using a rotary flash evaporator and stored in the refrigerator. All total of nine (9) extracts were prepared, and out of these nine extracts, the phytochemical analysis suggested the presence of phytosterol in the chloroform extract of the stem (SCDO). Therefore, the isolation was carried out for this particular extract. Result: The isolated compound was subjected to crystallization, and the melting point was found to be 242-244⁰C. The structure of the compound was determined by spectral analysis like U.V., I.R., N.M.R., Mass Spectroscopy, and lastly, X-Ray Crystallography. All the spectral data proved the compound to be a phytosterol/steroids "Dendrosterone" (molecular formula=C29H44O5; molecular weight = 472.66). Conclusion: This isolated steroid was further screened for antimicrobial activity (for the first time) against different gram +ve, and -ve strains of bacteria and other strains of fungi, and this phytosterol was found to be active against B.subtilis, and C. albincas among all the organisms tested.